2011
DOI: 10.3109/07357907.2010.543365
|View full text |Cite
|
Sign up to set email alerts
|

SMARCA5Methylation and Expression in Gastric Cancer

Abstract: Here, we first evaluated SMARCA5 expression and promoter DNA methylation in gastric carcinogenesis. Immunohistochemistry and methylation-specific PCR were analyzed in 19 and 48 normal mucosa and in 52 and 92 gastric cancer samples, respectively. We observed higher immunoreactivity of SMARCA5 in gastric cancer samples than in normal mucosa. Moreover, SMARCA5 promoter methylation was associated with the absence of protein expression. Our findings suggest that SMARCA5 has a potential role in proliferation and mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 26 publications
1
23
0
2
Order By: Relevance
“…The protein is mainly involved in chromatin remodeling and regulation of transcription. Its deregulation has been described in gastric cancer [79]. More recently the possibility of SMARCA5 to produce a fusion transcript in extraskeletal Ewing sarcoma/primitive neuroectodermal tumor has been described.…”
Section: Ews Translocation Partners In Cancermentioning
confidence: 99%
“…The protein is mainly involved in chromatin remodeling and regulation of transcription. Its deregulation has been described in gastric cancer [79]. More recently the possibility of SMARCA5 to produce a fusion transcript in extraskeletal Ewing sarcoma/primitive neuroectodermal tumor has been described.…”
Section: Ews Translocation Partners In Cancermentioning
confidence: 99%
“…Finally, 34 studies lacked usable data that correlated telomerase or hTERT with lymph node status or TNM stage to create 2x2 tables. Thus, a total of 18 eligible studies related to GC patients were finally identified in our meta-analysis with good agreement between reviewers (κ=0.73) (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) (Fig. 1).…”
Section: Selection and Characteristics Of The Studiesmentioning
confidence: 99%
“…Although research was conducted at tertiary referral centers, almost all studies were performed in Asia and one in South America (22). Sample size varied from 20 to 95 participants, and the average age across all of the studies was 59.3 years, with a variation ranging from 32 to 89 years.…”
Section: Selection and Characteristics Of The Studiesmentioning
confidence: 99%
“…More recently, SNF2H was identified as a fusion partner of EWSR1 in Ewing sarcoma/primitive neuroectodermal tumors, and the tumorigenic potential of the chimeric protein was documented (46). Furthermore, higher levels of SNF2H have been reported in gastric cancer than in normal mucosa, suggesting a role in malignancy (17).…”
mentioning
confidence: 99%